Endoscopic Diagnosis and Treatment of Bariatric Surgery Complications - Neto, Manoel Galvao; Quadros, Luiz Gustavo; Azor, Fernanda Oliveira (Digestive Disease Interventions, 2021)
Obesity has become a health problem that generates significant expenses for the health system worldwide. It is associated with chronic diseases—such as high blood pressure and diabetes—and some types of cancers. Bariatric surgery is the gold standard in the treatment of morbid obesity. Several endoscopic procedures have emerged to treat the complications of these surgeries in a less invasive way, reducing morbidity and mortality in these patients. This review aims to present the best trend in the endoscopic treatment of bariatric surgery complications.
Keywords: bariatric surgery; surgical complications; endoscopic treatment